Model Pengembangan Kurikulum Pendidikan Agama Islam Integratif di SMP Islam Yogyakarta - Himayatul Bariroh, Shofia; Hamami, Tasman (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Religious education in schools is felt to be less than optimal, because in practice it tends to only pay attention to cognitive aspects, while affective aspects do not get adequate attention. This imbalance results in a gap between knowledge and practice, between theory and practice in real life. Religious education in schools that are theoretical and normative in nature does not provide experience and practice of religious teachings in the lives of students. This study aims to reveal the development of Islamic religious education in an integrated manner in Islamic Junior High School Yogyakarta. This study uses a qualitative descriptive exploratory approach. Data collection techniques used in this study were observation, interviews and documentation. The results of the study indicate that Islamic religious education at the Yogyakarta Islamic Junior High School uses an integrative curriculum that combines the national curriculum with the Islamic boarding school curriculum. The implementation of the integrative curriculum is carried out through the integration of Islamic values ​​and linking the subject matter to the needs and values ​​of students' lives.